2015
DOI: 10.1186/s12879-015-0884-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the epidemiology, virology, and clinical features of influenza in China’s first severe acute respiratory infection sentinel surveillance system, February 2011 – October 2013

Abstract: BackgroundAfter the 2009 influenza A(H1N1)pdm09 pandemic, China established its first severe acute respiratory infections (SARI) sentinel surveillance system.MethodsWe analyzed data from SARI cases in 10 hospitals in 10 provinces in China from February 2011 to October 2013.ResultsAmong 5,644 SARI cases, 330 (6%) were influenza-positive. Among these, 62% were influenza A and 38% were influenza B. Compared with influenza-negative cases, influenza-positive SARI cases had a higher median age (20.0 years vs.11.0, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 7 publications
9
28
0
Order By: Relevance
“…It was very similar to the findings in Kenya, 26.7% [25] but lower than in Rwanda, 29.2% [26]. The influenza positivity rate for SARI samples was 3.1% which was low compared to findings in South Africa and China which reported 8% and 6% respectively [27, 28]. Our data showed that relatively the influenza positivity rate (27.9%) from outbreak sites was high.…”
Section: Discussionsupporting
confidence: 86%
“…It was very similar to the findings in Kenya, 26.7% [25] but lower than in Rwanda, 29.2% [26]. The influenza positivity rate for SARI samples was 3.1% which was low compared to findings in South Africa and China which reported 8% and 6% respectively [27, 28]. Our data showed that relatively the influenza positivity rate (27.9%) from outbreak sites was high.…”
Section: Discussionsupporting
confidence: 86%
“…The independent risk factors for mortality that were identified in this analysis, age ≥ 65 years and ICU admission, are consistent with those found in a limited number of studies reporting risk factors for mortality in all SARI patients [20,24]. Of 1790 adult and adolescent SARI patients in China, age ≥ 65 years was a significant risk factor for severe SARI outcomes (ICU admission or death) [21].…”
Section: Discussionsupporting
confidence: 86%
“…( 13 , 14 , 28 ) All three studies reported that influenza-associated hospitalization was higher among children of older age groups than among children aged < 2 years. Similar percentage of influenza-contributed respiratory hospitalizations among children < 18 years was also estimated from the global report ( 14 ) with 7.7% in developing countries and 8.5% in the WHO Western Pacific Region.…”
Section: Discussionmentioning
confidence: 99%
“…This case definition is more sensitive than the strict SARI definition used in the surveillance system during 2011–2013. ( 13 ) In most populated developing country hospitals, including hospitals that conduct surveillance associated with severe outcomes of a respiratory virus, busy clinicians examining patients describe the patient’s general condition related with ARI rather than list numerous signs and symptoms in detail. ( 30 ) For future surveillance on influenza-associated severe outcomes, if clinicians are responsible for case enrolment or if enrolment is based on patient chart review, standardization and simplification of the case definition are encouraged to improve case capture and surveillance quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation